2022
DOI: 10.1038/s41598-022-17280-2
|View full text |Cite
|
Sign up to set email alerts
|

Suicide versus homicide firearm injury patterns on trauma systems in a study of the National Trauma Data Bank (NTDB)

Abstract: Firearm related mortality in the USA surpassed all other developed countries. This study hypothesizes that injury patterns, weapon type, and mortality differ between suicide groups as opposed to homicide. The American College of Surgeons National Trauma Database was queried from January 2017 to December 2019. All firearm related injuries were included, and weapon type was abstracted. Differences between homicide and suicide groups by sex, age, race, and injury severity were compared using a Mann–Whitney test f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…This study found that firearms were the most likely mechanism [ 19 ]. Other trauma investigators have reported similarly high injury severity and mortality rates with self-inflicted trauma than other intentions [ 41 43 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This study found that firearms were the most likely mechanism [ 19 ]. Other trauma investigators have reported similarly high injury severity and mortality rates with self-inflicted trauma than other intentions [ 41 43 ].…”
Section: Discussionmentioning
confidence: 94%
“…Our findings that used the same data source as Truong et al, comport with these findings of high mortality [ 40 ]. General trauma literature has similarly found higher severity indices and mortality for firearms injury [ 41 , 42 ] and a propensity for self-inflicted firearms injuries to involve the head and face [ 41 , 43 ]. A recent study used CDC data and heat maps from 1990 to 2021 to evaluate trends in demographic and regional disparities in firearms-related mortality [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this trend was no longer apparent after adjustment. Given the low survivability associated with many self-inflicted firearm injuries, 39 this finding may be more reflective of the increasing incidence of these injuries rather than overall trauma center performance. 40,41 The present study did not demonstrate an increase in self-inflicted injuries over time, but given the increased likelihood of death on scene, the data likely does not reflect the totality of these injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The highest rates of firearm mortality have been reported among non-Hispanic Black patients 27. Intent for firearm injuries has also differed, where self-inflicted firearm injuries are more common in older white men and assault-related firearm injuries were more common in younger, non-Hispanic Black individuals compared with Hispanic or non-Hispanic White individuals 27 28. Firearm violence is also influenced by geospatial patterns, including neighbourhood characteristics and social networks 29–31.…”
Section: Discussionmentioning
confidence: 99%